Acute Exercise Improves Prefrontal Cortex but not Hippocampal Function in Healthy Adults. (19th November 2015) - Basso, Julia C.; Shang, Andrea; Elman, Meredith; Karmouta, Ryan; Suzuki, Wendy A.
Abstract: The effects of acute aerobic exercise on cognitive functions in humans have been the subject of much investigation; however, these studies are limited by several factors, including a lack of randomized controlled designs, focus on only a single cognitive function, and testing during or shortly after exercise. Using a randomized controlled design, the present study asked how a single bout of aerobic exercise affects a range of frontal- and medial temporal lobe-dependent cognitive functions and how long these effects last. We randomly assigned 85 subjects to either a vigorous intensity acute aerobic exercise group or a video watching control group. All subjects completed a battery of cognitive tasks both before and 30, 60, 90, or 120 min after the intervention. This battery included the Hopkins Verbal Learning Test-Revised, the Modified Benton Visual Retention Test, the Stroop Color and Word Test, the Symbol Digit Modalities Test, the Digit Span Test, the Trail Making Test, and the Controlled Oral Word Association Test. Based on these measures, composite scores were formed to independently assess prefrontal cortex- and hippocampal-dependent cognition. A three-way mixed Analysis of Variance was used to determine whether differences existed between groups in the change in cognitive function from pre- to post-intervention testing. Acute exercise improved prefrontal cortex- but not hippocampal-dependent functioning, with no differences found between delay groups. Vigorous acute aerobic exercise has beneficial effects on prefrontal cortex-dependent cognition and these effects can last for up to 2 hr after exercise. ( JINS, 2015, 21, 791–801)